Education for Sustainable Development in Primary School: Improvement of Students' Ecocriticism Skills - Ahmet Tekbiyik; Mustafa Celik (Seyit Ahmet Kıray, 2019)
Ecocriticism analyzes the symbolic meanings attributed to nature and the mindsets created by these meanings through interpreting literature and cultural texts from an environmental perspective. The individuals who have gained ecocriticism skills are expected to create an awareness concerning possession of a distinctive value and to direct towards a non-anthropocentric understanding from an anthropocentric understanding. The purpose of this study is to develop ecocriticism skills of primary school students in the third grade. Action research design has been used in this study. A total of 15 students composed of 8 females and 7 males participated in the study. Data of the study were obtained with rhetorical discussion, analytical discussion, mind maps, and drawings. Following the implementations composed of discussions, mind maps and drawings, it has been determined that the implementations develop the ecocritical inquiry skills of students.